2021
DOI: 10.1177/0145561321991349
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Using Bioglue in Nasal Septal Surgery

Abstract: Objectives: Nasal septal surgery is one of the most common surgical procedure performed by otolaryngologists. Nasal packs are used for bleeding control, prevention of septal hematoma, replacement of mucoperichondrial flaps, and stabilization of the septum after nasal septal surgery. The aim of this study was to investigate the effects of albumin-glutaraldehyde–based tissue adhesive (Bioglue), which can be used as an alternative to nasal pack on the nasal septum after experimental nasal septum surgery. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Their research indicated that a surgical procedure on the nasal septum resulted in segmental cartilage injury from BioGlue. 9 Singh et al reported wound complications following BioGlue application and recommended primary drainage, debridement, and removal of all BioGlue residues. 10 Singh and Wales cautioned against the use of BioGlue for hemostasis due to its adhesive and sealing properties.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Their research indicated that a surgical procedure on the nasal septum resulted in segmental cartilage injury from BioGlue. 9 Singh et al reported wound complications following BioGlue application and recommended primary drainage, debridement, and removal of all BioGlue residues. 10 Singh and Wales cautioned against the use of BioGlue for hemostasis due to its adhesive and sealing properties.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Albumin-based TAs are used to seal pulmonary air leaks [ 87 ] and to perform nephron-sparing [ 88 ], cardiac [ 89 ], nasal septal [ 90 ], proximal aortic [ 81 ], splenic [ 91 ], and inguinal hernia surgeries [ 92 ]. However, these TAs cannot control active bleeding; therefore, they can be used to adhere only to a bloodless area.…”
Section: Representative Examples Of Polymeric Tasmentioning
confidence: 99%